The phenomenon of begging between representing society and legal and religious legislation - SABKHAOUI, Khadidja; BOUHENIKA, Nadhir (Social Sciences Journal)
This article deals with one of the social phenomena produced by the Algerian society as a result of the social change that touched the various systems and had a clear impact on social life. It carries two different aspects of begging, and each point of view has its own justifications. There are those who justify begging and there are those who denounce it. We have shown this through some proverbs and popular Algerian wisdom entrenched in the memory of society. Scattered have their place in all, and this is by addressing the position of the Algerian positive legislation, and the position of the Islamic legislation of begging, to finally reach that it is considered a crime punishable by law as well as prohibited by Sharia, and this is because it humiliates human dignity in particular, and distorts the image of society in general.